Investigating computed tomography radiographers’ expertise in responding to severe contrast media reactions: a cross-sectional study - Yasser H. Hadi; Mahmoud H. Aljuaid; Nourah A. Alotaibi; Fatimah K. Altalhi; Hussam M. Ali; Mosaab G. Alrefaei; Abdulrahman I. Abu Aqil; Moram A. Fagiry; Hamid Osman; Mustafa Mahmoud (BMC Medical Education)
Abstract Background The use of intravenous contrast media (IVCM) in computed tomography (CT) scans enhances image quality by improving detail and accuracy, which is crucial for diagnosing complex medical conditions. While IVCM does provide notable benefits, it also carries the risk of rare but potentially life-threatening adverse reactions. The aim of this study was to evaluate the expertise and preparedness of CT radiographers in managing severe adverse reactions to IVCM. Furthermore, the research seeks to examine how variables such as professional experience, training, and practice location affect the competence of CT radiographers in managing such occurrences. Methods This cross-sectional survey assessed the knowledge and preparedness of Saudi CT radiographers in managing severe IVCM reactions. Following ethical approval from the Institutional Review Board (IRB) at King Abdullah Medical City (KAMC), an electronic survey was piloted with 15 radiographers for validation before distribution. Participants, recruited via snowball sampling through social media and professional networks, were accredited CT radiographers actively practicing in Saudi Arabia. The study examined knowledge variations based on experience, training, and practice setting. Although the target was 300 participants, 241 responses were obtained, providing meaningful insights into radiographers’ competencies in contrast reaction management. Results We assessed CT radiographers’ knowledge and preparedness in managing severe IVCM reactions using different scales, achieving a high response rate of 97.2%. The overall knowledge measure demonstrated strong reliability, with a Cronbach’s alpha coefficient of 0.854. The average knowledge score was 25.02 out of 40. Participants exhibited sufficient knowledge in various areas, with the highest proportion (93.4%) demonstrating awareness of precautionary measures for IVCM use. However, only 22.0% of participants attained consistent knowledge across all five assessed knowledge categories. Conclusions This study demonstrates the importance of continuous professional development and structured training, specifically following international criteria, in improving the understanding of CT radiographers in Saudi Arabia about the management of adverse reactions to contrast media. Senior experts, as well as those with international training, demonstrate exceptional expertise.